A Survey of User Preferences on Biometric Authentication for Smartphones - Syabila Zabidi, Nur; Mohd Norowi, Noris; Wirza O.K. Rahmat, Rahmita (International Journal of Engineering and Technology, 2018)
The search for improving users’ security needs, awareness and concerns in the context of mobile phones still has been conducting in today’s society. Biometric systems identify a person or verify the identity of a person using purportedly unique physical traits or behaviour of that individual. In order to understand user requirements for biometric authentication, it is important to focus on several key issues, including the importance of smartphones in implementing biometric authentication, users’ general knowledge and perception towards biometric authentication, and users’ trust and practice when using different biometric technology for securing their smartphone’s data. A preliminary study in the form of an online survey was conducted. The idea of this study was to conduct a survey on users about their general knowledge and perceptions towards different biometric authentication on smartphones. The results of the study indicate that smartphone is an important tool in implementing biometric authentication. Moreover, users knew what biometric technology is and they are not reluctant to use them. Furthermore, users knew how to protect their smartphone’s data and practice the related preventions. The results are expected to give an insight of deploying biometric technology into mobile devices and further researching onto others biometric authentication.